2009
DOI: 10.1242/jeb.019778
|View full text |Cite
|
Sign up to set email alerts
|

Swimming for your life: locomotor effort and oxygen consumption during the green turtle (Chelonia mydas) hatchling frenzy

Abstract: SUMMARY Swimming effort and oxygen consumption of newly emerged green turtle Chelonia mydas hatchlings was measured simultaneously and continuously for the first 18 h of swimming after hatchlings entered the water. Oxygen consumption was tightly correlated to swimming effort during the first 12 h of swimming indicating that swimming is powered predominantly by aerobic metabolism. The patterns of swimming effort and oxygen consumption could be divided into three distinct phases: (1) the rapid fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 17 publications
6
59
0
Order By: Relevance
“…However, numerous studies have highlighted strong and linear relationships between locomotion effort and oxygen consumption for a broad range of taxa (see Schmidt-Nielsen, 1972;Mayhew, 1977;Booth 2009). Furthermore, in a recent study on post-breeding SES females, Genin et al (A.G., G.R., J.J., B.P., N. El Skabi, J.V.-G. and C.G., unpublished) found that surface interval duration, related to the number of breaths taken, was highly correlated to the dive duration and the overall swimming effort of the previous dive.…”
Section: Swimming Effortmentioning
confidence: 99%
“…However, numerous studies have highlighted strong and linear relationships between locomotion effort and oxygen consumption for a broad range of taxa (see Schmidt-Nielsen, 1972;Mayhew, 1977;Booth 2009). Furthermore, in a recent study on post-breeding SES females, Genin et al (A.G., G.R., J.J., B.P., N. El Skabi, J.V.-G. and C.G., unpublished) found that surface interval duration, related to the number of breaths taken, was highly correlated to the dive duration and the overall swimming effort of the previous dive.…”
Section: Swimming Effortmentioning
confidence: 99%
“…During the swim frenzy, hatchlings usually alternate between bouts of a high thrust production, lift-based movement of the fore-flippers, the 'power stroking' gait, and bouts of a lower thrust production 'dog paddling' gait in which alternate movement of all four flippers in a paddle-like motion produces dragbased thrust (Salmon and Wyneken, 1987;Wyneken and Salmon, 1992). Power stroking bouts typically last between 2 and 20s and are interspersed with short periods of dog paddling (1-5s), when hatchlings surface to breathe (Salmon and Wyneken, 1987;Burgess et al, 2006;Booth, 2009) (Fig.1). Power stroke rates and oxygen consumption are highest immediately after the hatchlings enter the water and decline as the swim frenzy progresses (Salmon and Wyneken, 1987;Wyneken and Salmon, 1992;Burgess et al, 2006;Booth, 2009;Ischer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Power stroking bouts typically last between 2 and 20s and are interspersed with short periods of dog paddling (1-5s), when hatchlings surface to breathe (Salmon and Wyneken, 1987;Burgess et al, 2006;Booth, 2009) (Fig.1). Power stroke rates and oxygen consumption are highest immediately after the hatchlings enter the water and decline as the swim frenzy progresses (Salmon and Wyneken, 1987;Wyneken and Salmon, 1992;Burgess et al, 2006;Booth, 2009;Ischer et al, 2009). As power stroking bouts become less intense, dog paddling bouts become longer and resting periods may increase over time (Burgess et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations